2022
DOI: 10.3389/fonc.2022.779030
|View full text |Cite
|
Sign up to set email alerts
|

Incremental Value of Radiomics in 5-Year Overall Survival Prediction for Stage II–III Rectal Cancer

Abstract: Although rectal cancer comprises up to one-third of colorectal cancer cases and several prognosis nomograms have been established for colon cancer, statistical tools for predicting long-term survival in rectal cancer are lacking. In addition, previous prognostic studies did not include much imaging findings, qualitatively or quantitatively. Therefore, we include multiparametric MRI information from both radiologists’ readings and quantitative radiomics signatures to construct a prognostic model that allows 5-y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Moreover, imaging provides unique 3D information about neoplasm. These radiomics features can be leveraged to develop predictive models for survival and treatment failure (33)(34)(35)(36)(37)(38)(39)(40)(41)(42). The rationale behind this approach is that these images capture crucial information about the neoplasm phenotype and microenvironment (43).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, imaging provides unique 3D information about neoplasm. These radiomics features can be leveraged to develop predictive models for survival and treatment failure (33)(34)(35)(36)(37)(38)(39)(40)(41)(42). The rationale behind this approach is that these images capture crucial information about the neoplasm phenotype and microenvironment (43).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, imaging provides unique 3D information about the tumor. Studies have shown the clinical utility of CT and PET in predicting treatment outcomes for rectal and lung cancer patients 27 , 28 . The rationale behind this approach is that these images capture crucial information about the tumor phenotype and microenvironment 29 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have highlighted the potential of medical images in defining genetic mutations related to cancer and utilizing radiomics-based imaging biomarkers for outcome predictions [22][23][24] . Outcome prediction typically involves the use of classical statistical methodologies or Artificial Intelligence (AI) models trained on historical data encompassing genomic, epigenomic, and other omics data.…”
Section: Introductionmentioning
confidence: 99%
“…The rationale behind this approach is that these images capture crucial information about the tumor phenotype and microenvironment 21 . Recent studies have highlighted the potential of medical images in defining genetic mutations related to cancer and utilizing radiomics-based imaging biomarkers for outcome predictions 22 24 Outcome prediction typically involves the use of classical statistical methodologies or Artificial Intelligence (AI) models trained on historical data encompassing genomic, epigenomic, and other omics data. These models aim to uncover patterns or predictors associated with the specific outcome of interest, enabling personalized predictions for individual patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation